2017
DOI: 10.1109/tcst.2016.2547981
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Low-Frequency Electroacoustic Absorbers Through Hybrid Sensor-/Shunt-Based Impedance Control

Abstract: Abstract-This paper proposes a hybrid impedance control architecture for an electroacoustic absorber, that combines an improved microphone-based feedforward control with a currentdriven electrodynamic loudspeaker system. Feedforward control architecture enables stable control to be achieved, and current driving method discards the effect of the voice coil inductance. A method is given for designing the transfer function to be implemented in the controller, according to a target specific acoustic impedance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
74
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 12 publications
2
74
1
Order By: Relevance
“…Active control, when applied to Electroacoustic Resonators (ERs) to enable the adjustment of their impedance, was early considered for achieving broadband sound absorption in the low frequency range [1][2][3][4][5]. The concept offers a wide range of achievable acoustic impedances, including the synthesis of narrow-band single-degree of freedom (SDOF) resonators [5], or resonances with multiple degrees of freedom [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Active control, when applied to Electroacoustic Resonators (ERs) to enable the adjustment of their impedance, was early considered for achieving broadband sound absorption in the low frequency range [1][2][3][4][5]. The concept offers a wide range of achievable acoustic impedances, including the synthesis of narrow-band single-degree of freedom (SDOF) resonators [5], or resonances with multiple degrees of freedom [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, active control has also received a surge of interest as a tool for designing Acoustic Metamaterials (AMMs) that overcome the restrictions imposed by passive AMMs [9][10][11][12], thereby expanding the reach of metamaterial science to a wealth of nontrivial acoustic phenomena such as PT-symmetry scattering [13][14][15][16], wavefront shaping [17][18][19] and non-Hermitian wave control [20,21]. A notable technique for active impedance control uses an electroacoustic loudspeaker, whose acoustic impedance can be modified either by shunting its electric terminals with an engineered electric load [1,5,7], or by feeding back a current/voltage that would be pro- * xinxin.guo@epfl.ch † herve.lissek@epfl.ch ‡ romain.fleury@epfl.ch portional to a combination of sensed acoustic quantities [2,7,22]. In the field of Active Electroacoustic Resonators (AERs), most previous studies are carried out under the assumption that the involved acoustic parameters are small enough to ensure that they remain linear at low frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the concept of electroacoustic absorber has been introduced as an effective means of damping the duct modes, either using shunt loudspeaker technique [22,23], direct feedback control [24,25], or by self-sensing control of the loudspeaker impedance [26]. Rivet et al (2017) showed that a loudspeaker and a microphone nearby, both being connected by a model-based transfer function, can be used for matching the impedance of a loudspeaker diaphragm to a target specific acoustic impedance, which has the effect of damping the standing waves in an enclosure [27].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these techniques are based on the control of the boundary impedance, e.g., the impedance of a loudspeaker membrane or a moving panel. [5][6][7][8] They use pressure and velocity sensors to measure the impedance in front of the moving surface and correct it, such that the impedance matches the impedance of the incoming sound wave. This can be effective in ducts where the acoustic impedance is simple, but difficult in more general cases where the impedance is more complex.…”
Section: Introductionmentioning
confidence: 99%